Implementing CBR on The College Rankings Based on Webometrics with EPSBED’s Data and Webometrics Knowledge - Marzuki Marzuki; Maria Shusanti Febrianti; Ahmad Cucus; Agus Sukoco (International Conference on Engineering and Technology Development (ICETD), 2012)
inclusion of the name of a university in a ranking system, especially at the top level according to a specific community is important and worth doing. The consideration, including the entry of a university in the list of top universities, is an excellent starting point for the world to recognize the existence of higher education, to boost the image of the university, will also improve promotion, especially in student acquisition and external support.   Webometrics is one of the world university ranking system that can be enjoyed by universities in Indonesia. Of the publication in July 2009 a total of 39 universities and the publication in January 2010 as many as 57 universities ranked 6000 Indonesia succeeded in the world. This ranking technique to calculate the accessibility of university websites and publications on google schoolar as the ranking parameter. However, Webometrics do not Rank  its based on a study program of higher education. Indonesia has more than 3000 universities which have an operating permit and each university has a study program. Objectivity in the performance of a university can be controlled through the data formulated academic activities through program Evaluation Based Self-Evaluation Study (EPSBED). EPSBED Data published to the public through the website http: \ \ evaluasi.or.id. whereas until now Indonesia has not had a rating system.   Case-Based Approach Computing Reasoning (CBR), combined with machine learning algorithms its Nearest Neighbor (NN) as the ranking methodology that uses data EPSBED, then the ranking of a university system may be based on their individual study program.